Addiction, Modernity, and the City A Users' Guide to Urban Space - Smith, Christopher B.R (Routledge Advances in Sociology, 2016)
Examining the interdependent nature of substance, space, and subjectivity, this book constitutes an interdisciplinary analysis of the intoxication indigenous to what has been termed "our narcotic modernity." The first section - Drug/Culture - demonstrates how the body of the addict and the social body of the city are both inscribed by "controlled" substance. Positing addiction as a "pathology (out) of place" that is specific to the (late-)capitalist urban landscape, the second section - Dope/Sick - conducts a critique of the prevailing pathology paradigm of addiction, proposing in its place a theoretical reconceptualization of drug dependence in the terms of "p/re/in-scription." Remapping the successive stages or phases of our narcotic modernity, the third section -Narco/State - delineates three primary eras of narcotic modernity, including the contemporary city of "safe"/"supervised" consumption. Employing an experimental, "intra-textual" format, the fourth section -Brain/Disease - mimics the sense, state or scape of intoxication accompanying each permutation of narcotic modernity in the interchangeable terms of drug, dream and/or disease. Tracing the parallel evolution of "addiction," the (late-)capitalist cityscape, and the pathological project of modernity, the four parts of this book thus together constitute a users' guide to urban space.